Self-programming of information and its relationship to some offensive skills in volleyball among female students - Haneen Mohammed Hussein; Dr. Muna Talib Albadry (الرياضة المعاصرة, 2021)
The researchers used the descriptive approach with the two methods of survey study and correlational relations, and the research community was identified with the students of the College of Physical Education and Sports Sciences at the University of Kufa, their number was (26) students, then a sample of (20) students was chosen, then after that the scale was selected and applied and the offensive skills tests in volleyball On the research sample, then the scientific foundations were extracted and the appropriate statistical treatments were used to reach the results, after which the results were presented, analyzed and discussed. As for the objectives of the research, they included in several points, namely: